Student's Speaking Problems in Online Learning: A Systematic Research Review - Musleh Fajri; Rohmani Nur Indah (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2022)
This study used a systematic review, namely the research process by identifying previous research. Furthermore, this research applied a systematic analysis method that identifies the literature available on Google Scholar. This method has been utilized to deliver unique investigate as well as offer assistance analysts to fundamentally analyze, assess and synthesize complex thoughts. The five phases of systematic literature review are: 1) Framing questions for review 2) Relevant work 3) Assessing study quality 4) Summarizing the evidence 5) Interpret findings. From the results of the review on some of journals, it can be understood that there are students' problems in speaking class. Most of students have difficulties in terms of grammar, vocabulary, pronunciation based on reviewing of journal article. However, they also have problems in their psychology in learning speaking. Regarding online learning reviews, online learning is one of the alternative solutions for the learning process, including for students and teachers, during the COVID-19 pandemic. Although it raises some problems, for teachers and students, all parties must be ready to implement it. So, online learning has had both positive and negative impacts.